PRESENT: An Android-Based Class Attendance Monitoring System Using Face Recognition Technology - Salac, Djoanna Marie V. (International Journal of Computing Sciences Research, 2019)
Purpose – The study aimed to develop an Android-Based Class Attendance Monitoring Application using Face Recognition to make attendance checking and monitoring easier and faster. In addition, the system has also integrated the use of SMS technology to notify parents/guardians whenever the students attended a particular subject or class. In addition, the study also intended to evaluate the developed application in terms of functionality, usability, reliability, and portability. Method – The researcher utilized the incremental model. After the development phase, the application was evaluated by seventeen (17) faculty members from the College of Engineering and Computing Sciences. A validated evaluation questionnaire was used to rate the level of acceptability of the application based on ISO 9126 software quality and the level of satisfaction for its major features. For the statistical treatment of the data collected, Likert Scale, weighted mean and t -test were utilized by the researcher. Results – The results revealed that instructors find the existing way of checking attendance as time consuming and a tedious task. Furthermore, the respondents assessed the developed application as moderately acceptable in terms of functionality, reliability and usability while portability was rated as highly acceptable. With regards to the features, the respondents were very satisfied. The t-test also revealed that there is a significant difference between the level respondents’ level of acceptability on the existing and the proposed system. Conclusion – The researcher concluded that the developed application was useful and it can support the needs of the instructors to make attendance checking and monitoring easier, faster, and reliable. Recommendations – Due to its acceptable evaluation result, instructors should consider the use of this tool as an alternative to the existing process of checking and monitoring class attendance .  The developed system can be enhanced in terms of user design to make it more user-friendly. Research Implications – Classroom presence is important because this helps students to succeed in their academics when they attend class regularly. With the integration of different technologies such as Android, face recognition and SMS, the traditional way of checking class attendance can be made easier, faster, reliable and secured, thus improving classroom management.